NEW MODELS OF BULVER LANDSCAPING BASED ON GREEN ARCHITECTURE PRINCIPLES ARCHITECTURAL ELEMENTS - Sh. A. Egamberdiyeva; Sh. Z. Sokhibova (Bright Mind Publishing, 2025)
This in the article modern in urban planning the boulevards green architecture principles based on landscaping new models working exit according to scientific analysis and conceptual approaches The research purpose — ecological stability , microclimate optimization and public of places functional opportunities expansion through boulevard design architecture models and ecological efficiency Analysis international "Green Infrastructure", " Biophilic Urbanism", "Climate-Responsive Design", "Complete Streets" and "WSUD" (Water Sensitive Urban Design) principles based on take went . Results boulevard landscape ecological and architectural-compositional efficiency to increase aimed at new scientific the model offer will reach.
Keywords: Boulevard, green architecture, green corridor, biophilic design, smart- landscape, ecological stability.